On the work of Kharkiv prosthetists during the Great Patriotic War, its projection on the postwar period and the present day (to the 65th anniversary of the victory over fascism) - Dynnik, Oleksey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
On the basis of the documents, kept in Prof. Alexandr Panteleymonovich Kotov’s archives, the article describes the work of the Kharkiv Orthopaedic Factory during the Great Patriotic War. Its workers started manufacturing of prosthetic-orthopaedic products and provided medical-prosthetic aid to seriously wounded defenders of the Motherland in difficult conditions of evacuation (in Ordzhonikidze and Semipalatinsk). The article elucidates the part of Kotov A.P. in the organization of specialized hospitals in the rear as well as in making up and realizing “The Plan of Construction of Orthopaedic Industry in Ukraine” at the late war and post-war periods; the latter was the task of the People’s Commissariat of Health of the Ukrainian Soviet Socialist Republic. From the positions of the influence exerted by the feat of arms of Kharkiv prosthetists on the subsequent period, the main landmarks in the post-war development of the Kharkiv prosthetic-orthopaedic factory are described and the part of its leaders – the Hero of the Soviet Union Isaev V.V. and Zaika N.G. – is shown. The authors emphasize the part of Kotov A.P. in the development of scientific and practical aspects of prosthetic-orthopaedic aid in Ukraine and examine the advanced initiative of naming the Ukrainian Research Institute of Prosthetics, Prosthesis Making and Working Capacity Restoration after Prof. Kotov A.P.